(untitled) (Bangladesh Journal of Agricultural Research, 2023)
The nature of combining ability and heterosis were studied in an 8×8 diallel cross excluding reciprocals in maize for grain yield and yield contributing characters. Significant estimates of general combining ability (GCA) and specific combining ability (SCA) variances suggested the importance of both additive and non-additive gene actions for the expression of the traits studied. The variances for GCA Was found significant for days to pollen shedding, days to silking, plant height, ear height, 1000- grain weight and yield. SCA was significant for all the characters except yield. Non-significant SCA variance for yield suggests that this trait was predominantly controlled by additive type of gene action. Variances due to GCA were much higher in magnitude than SCA for all the characters indicating preponderance of additive gene effects for the inheritance of these traits. Parents CML431 (P4) and CML285 (P6) were the best general combiner for both high yield and parent CLG1837 (P7) and CML429 (P8) for earliness and dwarf plant type. Seven crosses CL02450×CML451 (P1×P5), CL02450×CLG1837 (P1×P7), CML551×CML431 (P2×P4), CML223×CML451 (P3×P5), CML431×CML451 (P4×P5), CML431× CML429 (P4×P8) and CML285× CLG1837 (P6× P7) exhibited positive SCA effects for grain yield. Considering, BARI Hybrid Maize-9 (BHM-9) as check, the percent heterosis for grain yield varied from -46.17 to 12.14%. Two crosses CML551×CML431 (P2×P4) and CML285× CLG1837 (P6× P7) exhibited significant and positive heterosis 12.14 and 10.77%, respectively over the check BHM-9 suggested their benefit cost ratio (BCR) study for developing high yielding hybrid varieties. Bangladesh J. Agril. Res. 47(1): 81-90, March 2022